Dietary Interventions, Cardiovascular Aging, and Disease: Animal Models and Human Studies. Issue 10 (13th May 2016) - Mirzaei, Hamed; Di Biase, Stefano; Longo, Valter D.
Abstract : Recent studies indicate that dietary interventions have the potential to prevent and even treat cardiovascular disease, which is the leading cause of death. Many of these studies have focused on various animal models that are able to recreate one or more conditions or elevate risk factors that characterize the disease. Here, we highlight macronutrient-focused interventions in both mammalian model organisms and humans with emphasis on some of the most relevant and well-established diets known to be associated with cardiovascular disease prevention and treatment. We also discuss more recent dietary interventions in rodents, monkeys, and humans, which affect atherosclerosis and cardiovascular diseases with focus on those that also delay aging.